Rap, langues, « québéquicité » et rapports sociaux de sexe : pratiques et expériences de rappeuses montréalaises d’origine haïtienne - Lesacher, Claire (Diversité urbaine, 2014)
In the stories recounting the early days of the rap scene in Montreal, actors of Haitian descent were particularly active on the rap scene: this is evident in rap texts, where frequent occurrences of Haitian Creole can be found. Considering this characteristic of Montreal rap, we propose a reflection on the issues around the visibility of Haitian migrants, and descendants of Haitian migrants, in Quebec public space by focusing on the practices and experiences of Montreal female rappers of Haitian descent. In this contribution, which aims at understanding the processes of hegemonization and minoritization at work in the Montreal and Quebec context, we will examine in particular how the vectors of differentiation involving language, “québéquicité” or gender, are manifested and reproduced in the media coverage of artistic productions.
Keywords: Haitian community; Rap; communauté haïtienne; gender; genre; languages; langues; « québéquicité »; “québéquicité”

Native Classical: Musical Modernities, Indigenous Research Methodologies and a Kanienkéha (Mohawk) Concept of Non:wa (Now) - Witzleben, John Lawrence (Université du Maryland, 2014)
In this dissertation I explore how Indigenous methodologies that foreground cultural advocacy, revitalization, and education can be articulated using Indigenous language and cultural metaphor in research on North American Indian composers. Toward this end, I apply the Kanienkéha (Mohawk) concept of "non:wa" or "now" that also refers to three modes of perception–the now of the past, the present, and the future–toward understanding the intersection of innovation and tradition in classical Native music. This research joins the existing discourse that critiques binary oppositions separating Indigenous tradition (as past) and innovation (as present and future). Through interviews, fieldwork, and musical analysis, I illustrate Native values of interconnectedness, relationality, continuity, politics, and soundscapes in the processes of Native composition as well as the resultant works, I explore how these, in turn, may be understood through the application of Indigenous research techniques. In collaboration with a cohort of contemporary musicians, I look primarily at two Navajo composers–Raven Chacon and Juantio Becenti–and examine my own work as a composer, performer, and ethnomusicologist of Kanienkéha descent to explore the following questions: How can the topic of classical Native music best be served by using Indigenous methodologies in fieldwork, research, and representation and What is classical Native Music and is it different from other contemporary classical music styles? Drawing on the teachings of Indigenous dotahs (elders/teachers), the scholarship of ethnomusicologists, and examining oral and written tradition while using language and cosmology as cultural metaphors, I present a variety of possibilities for looking at Indigenous music through Indigenous eyes. Rather than offering a set of conclusions, I offer a set of tools for discussion and reflection: 1) how we might understand a definition of classical Native music; 2) how we are part